Hydrocarbons and heavy metals in the different sewer deposits in the Te Marais’ catchment (Paris, France): stocks, distributions and origins - Rocher, V.; Azimi, S.; Moilleron, R.; Chebbo, G. (Science of the Total Environment, 2004)
The knowledge of the pollution stored in combined sewers is of prime importance in terms of management of wet weather flow pollution since sewer deposits play a significant role as source of pollution in combined sewer overflows. This work, which focused on the hydrocarbon (aliphatic and aromatic hydrocarbons) and metallic (Fe, Zn, Pb, Cu and Cd) pollution fixed to the different kinds of sewer deposits (gross bed sediment [GBS], organic layer [OL] and biofilm), was performed in order to provide a complete overview of the contaminant storage in the ’Le Marais’ combined sewer (Central Paris, France). Firstly, our results have shown that, for all kinds of pollutants, a major part was stored in the GBS (87 to 98%), a lesser part in the OL (2 to 13%) and an insignificant part in the biofilm (< 1%). These results demonstrated that the potential contribution of biofilm to wet weather pollution was negligible compared to the OL one. Secondly, the investigation of hydrocarbon fingerprints in each deposit has provided relevant information about contamination origins: (1) aliphatic hydrocarbon distributions were indicative of petroleum input in the GBS and reflected a mixture of biogenic and petroleum inputs in the OL and biofilm, (2) aromatic hydrocarbon distributions suggested an important pyrolytic contamination in all the deposits. Finally, the study of pollutant fingerprints in the different deposits and in the suspended solids going through the collector has shown that: (1) the suspended solids were the major component of OL and biofilm while urban runoff seemed to be the main transport mechanism introducing pollutants in the GBS and (2) the residence times in sewer of OL and biofilm were quite short compared to those for GBS. (C) 2003 Elsevier B.V. All rights reserved.